Metal composition and method for preparing the same

By mixing the metal-containing unit with deionized water and adjusting the pH value, a refined metal-containing unit is formed, which solves the problems of impurity pollution and side reactions of high-temperature distillation, and achieves efficient impurity removal and industrial production of semiconductor materials.

CN108602844BActive Publication Date: 2025-01-10PRYOG LLC
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN201580084943.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2015-09-29
Publication Date
2025-01-10
Estimated Expiration
2035-09-29

AI Technical Summary

Technical Problem

In the prior art, metal-containing units have high content of impurities contamination during the preparation process, resulting in yield loss and corrosion problems of semiconductor devices, and the high-temperature distillation method produces side reactions, limiting the industrial feasibility of the materials.

Method used

By mixing the metal-containing unit with deionized water, adjusting the pH to a range of 2 to 5.5, forming refined metal-containing units, reducing yield impurities, and drying at a temperature below 200°C, further by filtration and etching technology Prepare a patterned substrate.

Benefits of technology

It significantly reduces the yield impurity content, improves the purity and industrial feasibility of the material, reduces the generation of side reactions, and enhances the performance and production efficiency of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN108602844B_ABST
    Figure CN108602844B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method of forming a refined metal-containing unit by reducing yield impurities with acidified deionized water. Another embodiment is a composition comprising a refined metal-containing unit. Another embodiment is a method of forming a patterned substrate by depositing a composition comprising a refined metal-containing unit on a substrate, drying a film comprising the refined metal-containing unit, exposing the film comprising the refined metal-containing composition to an actinic radiation source, and transferring a pattern to a substrate. Embodiments of the present disclosure can be used to make a patterned substrate by direct or indirect pattern transfer from a film comprising a refined metal-containing unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosed embodiments relate to methods of preparing refined metal-containing units and their use in forming thin films, patterned thin films, and three-dimensional objects or articles used in making semiconductor devices. Background of the Invention

[0003] The use of metal-containing film-forming materials and their applications are well known. For example, U.S. Pat. No. 7,692,424, U.S. Pat. No. 7,888,441, U.S. Pat. No. 8,648,157, U.S. Pat. No. 8,709,705, and U.S. Pat. No. 8,802,346 describe metal-containing units that react to form ligands and become insoluble in organic solvents when exposed to radiation or heat and are capable of direct patterning. Hill et al. describe direct patterning into metal-containing materials in U.S. Pat. No. 5,534,312 and U.S. Pat. No. 7,176,114, wherein the metal complex is photosensitive and undergoes a low temperature reaction in the presence of light of a specific wavelength that renders the exposed portion insoluble in the solvent / developer. Commonly used metal-containing units for this application are Ti, Hf, and Zr. These materials are often contaminated with unacceptably high levels of impurities, such as ions of sodium, aluminum, iron, calcium, magnesium and chloride (U.S. Pat. No. 5,002,749 to Recasens et al., Yamagata, C., Andrade, JB, Ussui, V., Lima, NB and Paschoal, JOA “High purity zirconia and silica powders via wet process: alkali fusion of zirconsand”, Materials Science Forum, Vol. 591-593, 2008, pp 771-776).

[0004] Ion contamination causes Si device yield loss by creating defects in the electric field ( Handbook of Silicon Wafer Cleaning Technology, (Reinhardt, K. and Kern, W., eds.), William Andrew, NY (2008), pp 19). While metals such as calcium, potassium, sodium and iron can interfere with device electrical properties, other ionic impurities such as chloride ions also cause serious corrosion problems. Stowers et al. describe a photosensitive metal complex capable of direct patterning in U.S. Patent Application Publication 2011 / 029388, which contains an alkali metal and an ion such as chloride ion. A common method for purifying refractory metal precursors is multi-step distillation (Reuter et al. U.S. Patent 7,273,943). These distillations are generally carried out under high temperature and reduced pressure conditions. The high temperatures involved in the purification process can lead to undesirable side reactions and produce by-products. For example, distillation of zirconium alkoxides can lead to the formation of high molecular weight oligomers, which need to be carefully separated from pure zirconium alkoxides by fractional distillation. Distillation of reactive compounds used as ligands in metal complexes can lead to crosslinking and polymerization. Low overall product yields and high process costs severely limit the industrial feasibility of such materials for mass production. One object of the embodiments described herein is to provide a new method for preparing metal-containing units having reduced levels of yield impurities. In another aspect, the use of such refined metal-containing units for common semiconductor processes is also provided. SUMMARY OF THE INVENTION

[0006] One embodiment is a method of reducing yield impurities in a metalliferous unit (MU) to produce a refined metalliferous unit (RMU).

[0007] MU is represented by the structure I:

[0008]

[0009] Wherein M comprises a metal having a formal valence of 0-7 and is selected from Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As and Y; A, B and C groups can be selected to provide reactivity and compatibility with a variety of prepolymers and organic solvents, and to form optically transparent films or articles; ligand A contains a reactive functional group capable of undergoing a chemical reaction; w is 0 to 7; ligands B and C are selected with respect to metal-ligand photolysis and film-forming properties; x and y are 0 to 7.

[0010] In this embodiment, the RMU is formed by a process comprising mixing a solution of MU and deionized water, wherein the pH of the deionized water is adjusted to a range of about 2 to about 5.5.

[0011] In one aspect, a solution of MU is provided in an organic solvent system comprising at least one organic solvent miscible in water such that the MU solution and water form one phase.

[0012] The MU solution was added dropwise to the stirred deionized water so that the RMU formed a solid mass. The solid RMU thus formed was separated by decanting all the liquid, or by centrifugation, or by filtering through a suitable filter medium. The RMU was further dried in a vacuum oven at a temperature of less than 150° C. under reduced pressure. A portion of the RMU sample was subjected to yield impurity analysis.

[0013] In another aspect, a solution of MU is provided in an organic solvent system comprising at least one water-immiscible organic solvent. The water-immiscible organic solvent has low miscibility or even no miscibility in water, so that the MU solution and water form two separate phases when standing. This MU solution is mixed with deionized water adjusted to a pH in the range of about 2 to about 5.5. When mixing is stopped, the organic phase is separated from the aqueous phase. The aqueous phase is discarded. The RMU so formed remains in the organic phase. A small portion of the RMU solution so obtained is subjected to a yield impurity analysis.

[0014] In embodiments, the method reduces yield impurities to levels below 5000 ppb, or below 2500 ppb, or below 1000 ppb, or below 500 ppb for each yield impurity based on total RMU weight.

[0015] In embodiments, the method reduces each yield impurity by at least 15%, or at least 40%, or at least 75% of the initial yield impurity content.The following embodiments provide methods of using compositions comprising RMU in the manufacture of semiconductor devices.

[0016] Patterned substrates and doped patterned substrates are commonly used in the manufacture of semiconductor devices.

[0017] In another embodiment, a method for forming a patterned substrate is provided, the method comprising, a) providing RMU; b) preparing a composition comprising RMU; c) providing a substrate; d) depositing the composition on a substrate; e) drying the composition at a temperature below 200° C.; f) forming a pattern in a film comprising RMU; and g) transferring the pattern to a substrate by etching to produce a patterned substrate.

[0018] The composition comprising RMU may include additives such as catalysts or initiators, monomers, polymers, dyes or colorants, surfactants or leveling agents and adhesion promoters and solvents that impart film-forming properties. For example, an initiator or catalyst may be used to induce a chemical reaction in the RMU. Dyes may be used to adjust the absorbance of the deposited composition comprising RMU so that it absorbs more light at a specific wavelength of exposure. Solvents may be used to adjust the film thickness.

[0019] The substrate includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn, and W alone or in combination.

[0020] The pattern in the composition containing RMU can be formed by exposing the composition to a radiation source through a mask, a photomask or a mold. The unexposed portion of the composition is removed with a suitable developer. The radiation source can be selected from broadband light with a wavelength higher than 300nm, g-line at a wavelength of about 405nm, i-line at a wavelength of about 365nm, deep ultraviolet light at wavelengths of 248nm and 193nm, electron beam, X-ray beam or extreme ultraviolet light, alone or in combination.

[0021] Non-limiting examples of etching used to transfer patterns are dry etching and wet etching. Etching can take a single or multiple steps. Dry etching can be physical removal of material by plasma, chemical removal of material by gas, or a combination of physical and chemical removal (known as reactive ion etching). Wet etching involves contact with a liquid known to dissolve and remove materials.

[0022] Alternatively, a pattern in a composition comprising RMU may be produced by a method comprising 1) providing a photoresist; 2) depositing the photoresist on a film comprising RMU; 3) drying the photoresist at a temperature below 200° C.; 4) forming a pattern in the photoresist film; and 5) transferring the pattern to a film comprising RMU by etching.

[0023] In another embodiment, the present invention provides a method for forming a doped patterned substrate. The method includes a) providing RMU; b) preparing a composition comprising RMU; c) providing a substrate; d) depositing the composition on the substrate; e) drying the composition at a temperature below 200°C; f) forming a pattern in a film comprising RMU; and g) depositing a dopant into the exposed portion of the substrate using a reactive ion beam. Ion implantation introduces dopants to the exposed underlying substrate via a reactive ion beam.

[0024] Another embodiment is a method of forming a refined metal-containing unit (RMU), the method comprising: providing a metal-containing unit (MU), wherein MU is represented by structure I:

[0025]

[0026] wherein M comprises a metal having a formal valence of 0-7 and is selected from Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As, and Y; ligand A comprises a reactive functional group capable of undergoing a chemical reaction; w is 0 to 7; ligands B and C are selected, alone or in combination, from: oxygen, nitrogen, sulfur, or a halogen atom; hydroxyl, peroxide, phosphate, borate, tungstate, sulfate, silicate; substituted or unsubstituted linear, branched, or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl, or alkynyl; substituted or unsubstituted aryl; and -XR 1 , wherein X represents an organic functional group, such as oxy, sulfide, carboxyl, thiocarboxyl, sulfonyl, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1 represents a hydrogen atom, a substituted or unsubstituted straight chain, branched or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group, and a substituted or unsubstituted aryl or heteroaryl group; x and y are 0 to 7, and w+x+y is 2-7; MU is dissolved in an organic solvent, MU is present in an amount of about 5 wt% to about 70 wt% based on the total weight of MU and the organic solvent to form a MU solution, and the deionized water acidified solution is provided with a pH of less than 6.5 by adding an acid to the deionized water, the acid being composed of the structure R 2 -COOH means, where R 2 The RMU is selected from substituted or unsubstituted linear, branched or cyclic alkyl, alkenyl or alkynyl, alkyl ester, alkenyl ester, alkenyl ether or alkyl ether, substituted or unsubstituted aryl, alone or in combination. The method further comprises mixing the MU solution with an acidified solution of deionized water, and separating the RMU.

[0027] Another embodiment is a composition comprising a refined metal-containing unit (RMU) comprising at least one member selected from the group consisting of units represented by structure I:

[0028]

[0029] wherein M comprises a metal having a formal valence of 0-7 and is selected from Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As, and Y; ligand A comprises a reactive functional group capable of undergoing a chemical reaction; w is 0 to 7; ligands B and C are selected, alone or in combination, from: oxygen, nitrogen, sulfur, or a halogen atom; hydroxyl, peroxide, phosphate, borate, tungstate, sulfate, silicate; substituted or unsubstituted linear, branched, or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl, or alkynyl; substituted or unsubstituted aryl; and -XR 1 , wherein X represents an organic functional group, such as oxy, sulfide, carboxyl, thiocarboxyl, sulfonyl, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1 represents a hydrogen atom, a substituted or unsubstituted straight chain, branched or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group, and a substituted or unsubstituted aryl or heteroaryl group; x and y are 0 to 7, and w+x+y is 2-7, wherein the composition contains a reduced yield impurity. .

[0030] Another embodiment is a composition comprising a refined metal-containing unit (RMU) comprising at least one member selected from the group consisting of units represented by structure I:

[0031]

[0032] wherein M comprises at least one metal selected from the group consisting of Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As, and Y; ligand A comprises a reactive functional group capable of undergoing a chemical reaction; w is 1 to 7; ligands B and C are selected, alone or in combination, from oxygen, nitrogen, sulfur, a halogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl, or alkynyl group; a substituted or unsubstituted aryl group; and -XR 1 , wherein X represents an organic functional group, such as oxy, sulfide, carboxyl, thiocarboxyl, sulfonyl, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1represents a linear, branched or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group, and a substituted or unsubstituted aryl or heteroaryl group; and x and y are 0 to 6, wherein at least a portion of the metal-containing unit comprises at least one reactive functional group, and the composition comprises a reduced yield impurity.

[0033] Another embodiment is a method of forming a patterned substrate, the method comprising providing a refined metal-containing unit (RMU), and preparing a composition comprising the RMU, the RMU being represented by structure I:

[0034]

[0035] wherein M comprises at least one metal selected from the group consisting of Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As, and Y; ligand A comprises a reactive functional group capable of undergoing a chemical reaction; w is 1 to 7; ligands B and C are selected, alone or in combination, from oxygen, nitrogen, sulfur, a halogen atom, a substituted or unsubstituted linear, branched or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl, or alkynyl group; a substituted or unsubstituted aryl group; and -XR 1 , wherein X represents an organic functional group, such as oxy, sulfide, carboxyl, thiocarboxyl, sulfonyl, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1 represents a linear, branched or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group and a substituted or unsubstituted aryl or heteroaryl group; and x and y are 0 to 6, wherein at least a portion of the metal-containing unit comprises at least one reactive functional group. The method further comprises providing a substrate; depositing a composition comprising RMU to form a thin film on the substrate; drying the thin film comprising RMU at a temperature of less than 200° C.; forming a pattern in the thin film comprising RMU; and transferring the pattern to the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram illustrating a method of transferring a patterned thin film including RMU into a substrate.

[0038] Figure 2 Schematic diagram illustrating a method of patterning a thin film containing RMU through an organic layer and transferring it into a substrate.

[0039] Figure 3 Schematic diagram illustrating a method of transferring a patterned photoresist film into a substrate through a film pattern containing an RMU.

[0040] Figure 4 Schematic diagram illustrating a method of patterning a photoresist film through a film containing RMU and an organic layer pattern transfer into a substrate.

[0041] Figure 5 A schematic diagram illustrating ion implantation into a patterned substrate formed by pattern transfer from a patterned thin film containing RMU. DETAILED DESCRIPTION OF THE INVENTION

[0043] As used herein, the term "yield impurities" refers to ionic or non-ionic compounds that contaminate a device resulting in electrical yield loss. Non-limiting examples of yield impurities include metallic impurities and non-metallic impurities. Non-limiting examples of yield impurities include sodium, aluminum, iron, calcium, magnesium, potassium, zinc, copper, chromium, manganese, and chloride ions. For example, iron can exist in solution as metallic particles or as an ionic species.

[0044] The term "purifying" is used to denote the reduction of yield impurities.

[0045] As used herein, the term "ligand" refers to a molecule, ion or atom that is bound to a central atom of a coordination compound, chelate or other complex.

[0046] As used herein, the term "combination reaction" refers to the polymerization and / or crosslinking reaction of reactive functional groups. Crosslinking is usually chemical crosslinking, but in some cases it can be physical crosslinking. The combination reaction can be performed with RMUs and with RMUs and different components.

[0047] The term "reactive functional group" as used herein refers to functional groups such as epoxy, -SiH, -SH groups and ethylenically unsaturated functional groups such as vinyl, allyl, (meth)acryloyl groups. The compounding reaction includes the reaction of ethylenically unsaturated functional groups, the reaction involving ethylenically unsaturated functional groups and -SiH or -SH groups, and the reaction involving epoxy, -SiH and -SH groups.

[0048] As used herein, the prefix "(meth)acryloyl" refers to either acryloyl or methacryloyl.

[0049] The term "direct writing" refers to the process of scanning a focused light or electron beam to write a custom pattern on a film without a mask or mold. The light or electron beam changes the solubility of the photosensitive composition, thereby selectively removing the exposed or non-exposed areas of the photosensitive composition by immersion in a developer.

[0050] The term "photoresist" refers to any photosensitive composition that changes solubility in a developer when exposed to radiation (such as light or an electron beam). One type of photoresist, called a negative-working photoresist, becomes insoluble in the developer in the exposed areas. Another type of photoresist, called a positive-working photoresist, becomes soluble in the developer in the exposed areas.

[0051] The term "laser ablation" is the removal of material from a film or substrate by direct absorption of laser energy through a mask.

[0052] As used herein, the term "electronic device" is a device fabricated using microfabrication or nanofabrication techniques. Non-limiting examples of electronic or semiconductor devices include integrated circuits, microsensors, MEMS, inkjet nozzles, micro-optical devices, fiber optic telecommunications devices, flat panel displays, and laser diodes.

[0053] One embodiment is a method of reducing yield impurities in a metalliferous unit (MU) to produce a refined metalliferous unit (RMU).

[0054] MU is represented by the structure I:

[0055]

[0056] In Structure I, M comprises a metal having a formal valence of 0-7 and is selected from Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As and Y.

[0057] The ligand A contains a reactive functional group capable of chemical reaction; w is 0 to 7. The ligand A contains a reactive functional group such as a substituted or unsubstituted (meth)acryloyl group, a vinyl group, an allyl group, a styryl group, a cycloalkenyl group, an epoxy group, a SiH group, and a SH group.

[0058] Ligands B and C are selected, alone or in combination, from: oxygen, nitrogen, sulfur or halogen atoms; hydroxyl, peroxide, phosphate, borate, tungstate, sulfate, silicate; substituted or unsubstituted linear, branched or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl or alkynyl; substituted or unsubstituted aryl; and -XR 1 , wherein X represents an organic functional group, such as oxy, sulfide, carboxyl, thiocarboxyl, sulfonyl, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1represents a hydrogen atom, a substituted or unsubstituted straight chain, branched chain or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group and a substituted or unsubstituted aryl or heteroaryl group; x and y are 0 to 7. An example of an alkynyl group is an ethynyl group. An example of a substituted or unsubstituted straight chain, branched chain or cyclic alkyl ether group is succinic acid-terminated polyethylene glycol. An example of a substituted straight chain alkyl group is a pentafluoroethyl group. Examples of a carbanion are a 2,2-dimethyl-4,6-dioxo-1,3-dioxane-5-anion, a dicyanomethane anion, a cyclopenta-2,4-diene anion and a phenylacetylene anion.

[0059] In an embodiment, w is 1 to 7. In one aspect, the MU is similar to those described in published patent applications US Pat. No. 7,692,424, US Pat. No. 7,888,441, US Pat. No. 8,648,157, US Pat. No. 8,709,705, and US Pat. No. 8,802,346, which are incorporated herein by reference.

[0060] An example of MU may be Zr(O)(CH2CO2C(CH3))2, zirconyl dimethacrylate, in which case A is methacrylate, B is oxygen, w=2, x=1, y=0, and w+x+y=3.

[0061] Other non-limiting examples of metal-containing precursor units (MU) are zirconium (meth)acrylate, zirconium oxydi(meth)acrylate, zirconium butyl (meth)acrylate, zirconium carboxyethyl acrylate, zirconium vinyl acetate, zirconium oxydi(vinyl acetate), 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-carboxylic acid zirconium, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3,7 ]nonane-9-carboxylic acid (meth) acrylate zirconium, 6-(2-naphthylthio)bicyclo[2.2.1]heptane-2-carboxylic acid (meth) acrylate zirconium, [(1S,4R)-7,7-dimethyl-2-oxobicyclo[2.2.1]hept-1-yl] methanesulfonic acid 2-naphthalenethiol (meth) acrylate zirconium, hydroxysulfate oxyzirconium, hydroxytungstate oxyzirconium, hydroxyphosphate oxyzirconium, hydroxyborate oxyzirconium, hydroxysilicate oxyzirconium, hafnium (meth) acrylate, hafnium (meth) acrylate butoxy, hafnium di(meth) acrylate hafnium oxide, carboxyethyl acrylate hafnium, vinyl acetate hafnium and di(vinyl acetate) oxide, 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-carboxylic acid hafnium, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3,7] nonane-9-carboxylic acid (meth) acrylate hafnium, 6-(2-naphthylthio)bicyclo[2.2.1]heptane-2-carboxylic acid (meth) acrylate hafnium, [(1S,4R)-7,7-dimethyl-2-oxobicyclo[2.2.1]hept-1-yl] methanesulfonic acid 2-naphthalenethiol (meth) acrylate hafnium, hydroxysulfate oxyhafnium, hydroxytungstate oxyhafnium, hydroxyphosphate oxyhafnium, hydroxyborate oxyhafnium, hydroxysilicate oxyhafnium, (meth) acrylate titanium, (meth) acrylate butoxytitanium, di(meth) acrylate titanium oxide, carboxyethyl acrylate titanium, vinyl acetate titanium, di(vinyl acetate) oxide, 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-titanium carboxylate, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3,7 ]nonane-9-carboxylic acid (meth) acrylate titanium, 6-(2-naphthylthio)bicyclo[2.2.1]heptane-2-carboxylic acid (meth) acrylate titanium, [(1S,4R)-7,7-dimethyl-2-oxobicyclo[2.2.1]hept-1-yl] methanesulfonic acid 2-naphthalenethiol (meth) acrylate titanium, hydroxysulfate oxytitanium, hydroxytungstate oxytitanium, hydroxyphosphate oxytitanium, hydroxyborate oxytitanium, hydroxysilicate oxytitanium, bis(ethyl acetoacetate) diisopropoxytitanium, bis(2,4-pentanedione) diisopropoxytitanium, di-n-butoxydi(meth)acryloyloxygermane, tetracarboxyethylacryloyloxygermane, tetravinylacetoxygermane, tetra(meth)acryloyloxygermane, 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-carboxygermane, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3,7 ] nonane-9-carboxy tri(meth)acryloyloxygermane, 6-(2-naphthylthio)bicyclo[2.2.1]heptane-2-carboxy tri(meth)acryloyloxygermane, tantalum (meth)acrylate, tantalum (meth)acrylate butoxy, tantalum carboxyethyl acrylate, tantalum vinyl acetate, 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-carboxylic acid tantalum, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3,7 ] nonane-9-carboxylic acid (meth) acrylate tantalum, 6-(2-naphthylthio) bicyclo[2.2.1] heptane-2-carboxylic acid (meth) acrylate tantalum, hydroxysulfate tantalum, hydroxytungstate tantalum, hydroxyphosphate tantalum, hydroxyborate tantalum, hydroxysilicate tantalum, (meth) acrylate niobium, (meth) acrylate butyl niobium, carboxyethyl acrylate niobium, vinyl acetate niobium, 3-oxatricyclo[3.2.1.0 2,4 ] octane-6-carboxylic acid niobium, 2-bromo-5-oxo-4-oxatricyclo[4.2.1.0 3 ,7] nonane-9-carboxylic acid (meth) acrylate niobium, 6-(2-naphthylthio)bicyclo[2.2.1]heptane-2-carboxylic acid (meth) acrylate niobium, triphenylphosphine pentacarbonyl tungsten, tri(2-ethylhexanoate) cerium, bis(2-ethylhexanoate), yttrium tri(2-ethylhexanoate) and yttrium trihexanoate.

[0062] In embodiments, non-limiting examples of RMUs are zirconium, hafnium, and titanium compounds including (meth)acrylate or carboxyethyl acrylate ligands. In embodiments including (meth)acrylate or carboxyethyl acrylate ligands, additional ligands may also be present.

[0063] In this embodiment, RMU is formed by a process comprising mixing a solution of MU and deionized water, wherein the pH of the deionized water is adjusted to a range of about 2 to about 5.5. The pH of the deionized water used is adjusted by adding a solution of R 2 COOH represents the acid adjustment, where R 2 R is selected from substituted or unsubstituted straight chain, branched chain or cyclic alkyl, alkenyl or alkynyl, alkyl ester, alkenyl ester, alkenyl ether or alkyl ether, alone or in combination; substituted or unsubstituted aryl. 2 Non-limiting examples of R are methyl, trifluoromethyl, ethyl, pentafluoroethyl, propyl, heptafluoropropyl, butyl, vinyl, prop-2-enyl, 1,1,1-trifluoroprop-2-enyl, (2-acryloyloxy)ethyl, and phenyl. 2 Non-limiting examples of COOH are acetic acid, trifluoroacetic acid, heptafluorobutyric acid, acrylic acid, methacrylic acid, α-trifluoromethylacrylic acid, 2-carboxyethyl acrylate, and benzoic acid.

[0064] The deionized water used in the embodiments is described in ASTM D5127, and the resistivity was measured to be >12 MΩ-cm.

[0065] In one aspect, a solution of MU is provided in an organic solvent system comprising at least one organic solvent miscible in water such that the MU solution and water form one phase. Non-limiting examples of such water-miscible organic solvents are methanol, ethanol, n-propanol, isopropanol, tert-butyl alcohol, 1-methoxy-2-propanol, 2-propoxyethanol, 2-butoxyethanol, 2-ethoxyethyl ether, 2-butoxyethyl ether, dimethyl sulfoxide, gamma-butyrolactone, acetonitrile, ethyl lactate, N-methylpyrrolidone, dimethylformamide, tetrahydrofurfuryl alcohol, tetrahydrofuran, and acetone. Such water-miscible organic solvents are selected from the above alone or in combination.

[0066] A typical concentration range for the MU solution is from about 5 wt % to about 70 wt % MU based on the total weight of MU and organic solvent.

[0067] The MU solution can be filtered by microfiltration, ultrafiltration and nanofiltration techniques. The pore size of the membrane filter involved in the filtration technique can be about 0.001 to about 25 microns, or about 0.05 to about 10 microns, or about 0.1 to about 5 microns.

[0068] The MU solution was added dropwise to the stirred deionized water so that the RMU formed a solid mass. The solid RMU thus formed was separated by decanting all the liquid, or by centrifugation, or by filtering through a suitable filter medium. The RMU was further dried in a vacuum oven at a temperature of less than 150° C. under reduced pressure. A portion of the RMU sample was subjected to yield impurity analysis.

[0069] The above process can be repeated until the remaining impurities of each yield are less than 5000 ppb based on the weight of RMU solids. To repeat the process, solid RMU is dissolved in a water miscible solvent system.

[0070] The formed RMU precipitate is optionally dissolved in an additional organic solvent having a boiling point of 115° C. or higher. Non-limiting examples of such additional organic solvents are 2-heptanone, cyclopentanone, cyclohexanone, 1-methoxy-2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 4-methyl-2-pentanol, ethylene glycol monoisopropyl ether, 2-propoxyethanol, 2-butoxyethanol, 2-ethoxyethyl ether, 2-butoxyethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, 1-methoxy-2-propyl acetate , 2-ethoxyethyl acetate, 1,2-dimethoxyethane ethyl acetate, cellosolve acetate, methyl lactate, ethyl lactate, n-butyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, tetrahydrofurfuryl alcohol, tetraethylene glycol, 4-hydroxy-4-methyl-2-pentanone, 4-methyl-2-pentanone, γ-butyrolactone, dimethyl sulfoxide, dimethylformamide and N-methyl-2-pyrrolidone. Such organic solvents are selected from the above alone or in combination.

[0071] In another aspect, a solution of MU is provided in an organic solvent system comprising at least one water-immiscible organic solvent. The water-immiscible organic solvent has low miscibility or even no miscibility in water, so that the MU solution and water form two separate phases when standing. This MU solution is mixed with deionized water adjusted to a pH in the range of about 2 to about 5.5, as described above. When mixing is stopped, the organic phase is separated from the aqueous phase. The aqueous phase is discarded. The RMU so formed remains in the organic phase. A small portion of the RMU solution so obtained is subjected to a yield impurity analysis.

[0072] Non-limiting examples of water-immiscible organic solvents are ethyl acetate, propyl acetate, butyl acetate, 1-methoxy-2-propyl acetate, n-butanol, 4-methyl-2-pentanol, hexane, heptane, toluene, 2-methyltetrahydrofuran, 2-butanone, 4-methyl-2-pentanone, 2-heptanone, cyclopentanone, cyclohexanone, methyl tert-butyl ether and cyclopentyl methyl ether. Such water-immiscible organic solvents can be selected from the above alone or in combination.

[0073] RMU can be isolated as a solution in a concentration range of about 1 wt % to about 90 wt % or about 15 wt % to about 85 wt % (intermediate range) or about 25 wt % to about 80 wt % (narrow range).

[0074] The above process can be repeated until the remaining impurities of each yield are less than 5000 ppb based on the weight of the RMU solids. To repeat the process, the RMU solution is mixed with additional deionized water adjusted to a pH in the range of about 2 to about 5.5.

[0075] The above method is effective for reducing yield impurities to a level of less than 5000 ppb, or less than 1000 ppb, or less than 500 ppb for each yield impurity based on the total weight of RMU. In an embodiment, the method reduces the total yield impurity content to a level of less than 500 ppb, or less than 100 ppb, or less than 50 ppb based on the total weight of RMU.

[0076] Both aspects of the embodiments providing the formation of the RMU process reduce each yield impurity by at least 15%, or at least 40%, or at least 75% of the initial yield impurity content. In embodiments, the method reduces the total yield impurity by at least 15%, or at least 40%, or at least 75% of the initial total yield impurity content.

[0077] The following embodiments provide methods of using compositions comprising RMU in processes used to manufacture semiconductor devices.

[0078] Patterned substrates and doped patterned substrates are commonly used in the manufacture of semiconductor devices.

[0079] In another embodiment, a method for forming a patterned substrate is provided, the method comprising, a) providing RMU; b) preparing a composition comprising RMU; c) providing a substrate; d) depositing the composition on a substrate; e) drying the composition at a temperature below 200° C.; f) forming a pattern in a film comprising RMU; and g) transferring the pattern to a substrate by etching to produce a patterned substrate.

[0080] The RMU is described in the above embodiments.

[0081] Compositions comprising RMU can be prepared by mixing with additives, such as catalysts or initiators, monomers, polymers, dyes or colorants, surfactants or leveling agents and adhesion promoters and solvents that give certain functional characteristics to the composition deposited on the substrate. For example, initiators or catalysts can be used to induce chemical reactions in RMU. Dyes or sensitizers can be used to adjust the absorbance of the deposited composition comprising RMU so that it absorbs more light at a specific wavelength of exposure. Solvents can be used to impart film-forming properties and adjust the thickness of the deposited composition.

[0082] The catalyst or initiator used in the composition comprising RMU induces a chemical reaction of the reactive functional groups of the RMU when activated by irradiation or heating. The photoactive catalyst or photoinitiator used in the composition is a compound that absorbs light at the exposure wavelength and is capable of catalyzing the chemical reaction of the RMU and / or other different components when the deposited composition or a portion of the deposited composition is exposed to light. Non-limiting examples of photoinitiators include 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone (Irgacure 184, available from Ciba Specialty Chemical), a mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone (Irgacure 500, available from Ciba Specialty Chemical), 2,4,4-trimethylpentylphosphine oxide (Irgacure 1800, 1850 and 1700, available from Ciba Specialty Chemical), 2,2-dimethoxy-2-acetophenone (Irgacure 651, available from Ciba Specialty Chemical), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Irgacure 819, available from Ciba Specialty Chemical), (2,4,6-trimethylbenzoyl)diphenylphosphine oxide (Lucerin TPO, purchased from BASF), ethoxy(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Lucerin TPO-L, purchased from BASF) and a mixture of phosphine oxide, α-hydroxy ketone and benzophenone derivatives (ESACURE KTO46, purchased from BASF).

[0083] Examples of photoactive catalysts are photoacid generators, ions or nonions, such as triphenylsulfonium trifluoromethanesulfonate (available from Aldrich, Catalog No. 526940) and 2-methyl-α-[2-[[(propylsulfonyl)oxy]imino]-3(2H)-thienylene]-benzeneacetonitrile (available from BASF as Irgacure PAG 103).

[0084] Non-limiting examples of catalysts or initiators for inducing the chemical reaction in the presence of heat include, but are not limited to, organic peroxides such as benzoyl peroxide, diacyl peroxides, peroxydicarbonates, alkyl peresters, alkyl peroxides, perketals, ketone peroxides, and alkyl hydroperoxides; azo compounds such as azobisisobutyronitrile and 1,1'-azobis(cyclohexanecarbonitrile); and thermal acid generators such as cyclohexyl tosylate and K-Cure 1040 (available from King Industries).

[0085] The above catalysts or initiators can be used alone or in combination. In embodiments where a catalyst or initiator is used, the amount used is up to about 20% by weight based on the weight of the RMU, or up to about 10% by weight based on the weight of the RMU, or up to about 6% by weight based on the weight of the RMU.

[0086] The composition comprising RMU may further contain prepolymer units (PU) comprising at least two reactive functional groups. The term PU refers to a monomer unit or oligomer, where oligomer refers to a combination of monomer units bonded together. PU may comprise a lot of monomer units and may further react to bond to the final material. Examples of these monomer units / oligomers are based on one or more of the following types: acrylate, ester, vinyl alcohol, carbamate, urea, imide, amide, carbaxazole, carbonate, pyranose, siloxane, urea-formaldehyde and melamine-formaldehyde. PU comprises at least two terminal and / or pendant reactive functional groups. These may participate in the chemical reaction with RMU. Examples of these terminal and pendant groups are vinyl, allyl, (meth) acryloyl, epoxy, SiH and –SH groups. The important criteria for selecting RMU and PU for this embodiment composition is that they are compatible with each other.

[0087] Non-limiting examples of PU include urethane acrylate oligomers. The term urethane acrylate oligomer refers to a class of compounds containing urethane bonds and having (meth)acrylate functional groups, such as urethane multi-(meth)acrylates, polyurethane (meth)acrylates, and polyurethane multi-(meth)acrylates. The types of urethane (meth)acrylate oligomers are described by Coady et al. in U.S. Pat. No. 4,608,409 and by Chisholm et al. in U.S. Pat. No. 6,844,950, and are incorporated herein by reference. Other non-limiting examples of PU include 1,6-hexanediol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, divinylbenzene, ethoxylated bisphenol A-di(meth)acrylate, diethylene glycol bis(allyl carbonate), trimethylolpropane tri(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta / Hexa(meth)acrylate, isocyanurate tri(meth)acrylate, bis(2-hydroxyethyl)-isocyanurate di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, (meth)acrylate-modified urea-formaldehyde, melamine-formaldehyde cellulose, and siloxanes with vinyl, allyl, (meth)acryloyl or hydrosilane terminal or pendant functional groups. Non-limiting examples of such siloxane PUs include vinyl-, epoxy- or (meth)acryloyl-terminated polyhedral oligomeric silsesquioxanes (POSS) (Hybrid Plastics codes OL1160, EP0409, MA0735 and MA0736), vinyl-containing siloxanes (CAS 68083-19-2, 68951-96-2, 225927-21-9, 67762-94-1, 68083-18-1, 597543-32-3, 131298-48-1 and 29434-25-1 with Gelest Code EDV-2025, VMS-005, VPE-005, VMS-T11, VTT-106 and MTV-124), hydride-containing siloxanes (CAS 70900-21-9, 68037-59-2, 69013-23-6, 63148-57-2, 68988-57-8 and 24979-95-1 with Gelest Code HDP-111).

[0088] In embodiments where PU is utilized, the amount used is up to about 100 weight percent by weight of the RMU, or up to about 50 weight percent by weight of the RMU, or up to about 25 weight percent by weight of the RMU.

[0089] The composition comprising RMU may also include nanoparticles selected from surface treated or untreated silicon oxide, titanium oxide, zirconium oxide, hafnium oxide, CdSe, CdS, CdTe, lanthanum oxide, niobium oxide, tungsten oxide, and strontium oxide, alone or in combination.

[0090] The composition comprising RMU may further comprise a comonomer having only one reactive functional group. Non-limiting examples of comonomers are (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, and hydroxyethyl (meth)acrylate.

[0091] The composition comprising RMU may also comprise a suitable solvent of about 1% weight to about 70% weight concentration range. The selection of the solvent for the preparation and its concentration is mainly determined by the type and coating method of the functionality added in RMU and / or the different components. The solvent should be inert, all components should be dissolved or evenly dispersed in the composition, should not experience any chemical reaction with the components, and should be able to be removed when dry after coating. The non-limiting example of a suitable solvent is 2-butanone, 3-methyl-2-butanone, 4-hydroxy-4-methyl-2-pentanone, 4-methyl-2-pentanone, 2-heptanone, cyclopentanone, cyclohexanone, 1-methoxy-2-propanol, 2-methoxyethanol, 2-ethoxyethanol, ethylene glycol monoisopropyl ether, 2-propoxyethanol, 2-butoxyethanol, 4-methyl-2-pentanol, tetraethylene glycol, 2-ethoxyethyl ether, 2-butoxyethyl ether, glycol monoethyl ether, glycol monomethyl ether , diethylene glycol dimethyl ether, 1-methoxy-2-propyl acetate, 2-ethoxyethyl acetate, 1,2-dimethoxyethane ethyl acetate, cellosolve acetate, methyl lactate, ethyl lactate, n-butyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, gamma-butyrolactone, tetrahydrofurfuryl alcohol, N-methyl-2-pyrrolidone, dimethylformamide, dimethyl sulfoxide, 1,4-dioxane, methanol, ethanol, 1-propanol, 2-propanol and butanol.

[0092] By combining RMU and any other suitable solvent, the composition comprising RMU is prepared. The method described in the above embodiment comprises preparing by mixing the different components of the suitable ratio used in the composition, until a uniform solution is obtained. The composition can be filtered by microfiltration, ultrafiltration and nanofiltration technology. The non-limiting example of suitable filter media includes PTFE, nylon, polypropylene, surface treated polyethylene or polypropylene, etc. The nominal pore size can be from about 0.001 to about 5 microns.

[0093] The substrate includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. Non-limiting examples of suitable substrates include silicon, silicon oxide, silicon nitride, silicon oxynitride, gallium arsenide, silicon carbide, aluminum, aluminum oxide, aluminum nitride, copper, tungsten, glass, fiber reinforced glass, ITO coated glass, quartz, indium tin oxide and titanium nitride. The substrate can be polished, roughened, pre-patterned, coated with conductive ink or doped. The substrate can have more than one layer, for example, an organic or cross-linked organic film, a silicon-containing layer or an inorganic hard mask can be deposited on the substrate surface before depositing a film containing a composition containing RMU.

[0094] The composition comprising RMU is deposited on the substrate by any conventional method. Non-limiting examples of coating methods are spin coating, spray coating, dip coating, scraper or scraper coating, slot die coating, lamination and dry film lamination. The composition can be deposited in the form of a film or a three-dimensional object product. The typical thickness of the film comprising RMU is from about 10nm to about several millimeters.

[0095] Drying the composition comprising RMU forms a uniform defect-free coating or film. An example of a drying step is heating the substrate at a temperature in the range of about 40° C. to 200° C. for about a few seconds to a few minutes. Non-limiting examples of film thickness ranges for films comprising RMU are between 1 nm and about 1 mm, or between 5 nm and about 500 μm, or between 10 nm and about 200 μm.

[0096] The pattern in the film containing RMU can be formed by exposing the film containing RMU to a radiation source through a mask, a photomask or a mold. Exposure can also be performed by direct writing. After exposure, the portion of the film containing RMU exposed to the radiation becomes insoluble in the developer. The unexposed portion of the composition is removed with a suitable developer.

[0097] After exposure, the film containing RMU is further subjected to one or more steps of baking at a temperature below 1400° C. or exposure to a plasma or ion beam source. For example, the exposed film containing RMU can be baked at a temperature below 200° C. before development and then heated to a temperature of 350° C. after development.

[0098] Examples of actinic radiation are light (broadband or specific wavelengths from about 0.01 nm to about 600 nm) and heat. Non-limiting examples of radiation sources may be selected from broadband light with a wavelength above 300 nm, g-line at a wavelength of about 405 nm, i-line at a wavelength of about 365 nm, deep ultraviolet light at wavelengths of 248 nm and 193 nm, electron beam, X-ray beam, or extreme ultraviolet light, either alone or in combination.

[0099] The total exposure time varies depending on the intensity of the radiation, the thickness and properties of the film containing the RMU. The exposure time may vary depending on the power of the radiation. The exposure time may be from 1 millisecond to about 30 minutes, or from about 1 millisecond to about 15 minutes, from about 1 second to about 5 minutes. The film containing the RMU may be exposed to the radiation, either in a solvent-containing state or in a solvent-free state after evaporating a portion of the solvent.

[0100] The developer can be applied to the substrate by spraying, dipping or slurrying. The total contact time with the developer can be from seconds to minutes. The time required to dissolve the unexposed area of ​​the composition depends on the type of non-aqueous solvent or aqueous solution. Non-limiting examples of solvents used as developers include non-aqueous solvents such as ethers, esters, ketones and alcohols. Non-limiting examples of non-aqueous solvents can be selected from 2-butanone, 3-methyl-2-butanone, 4-methyl-2-pentanone, 4-hydroxy-4-methyl-2-pentanone, 2-heptanone, cyclopentanone, cyclohexanone, 1-methoxy-2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 4-methyl-2-pentanol, ethylene glycol monoisopropyl ether, 2-propoxyethanol, 2-butoxyethanol, 2-ethoxyethyl ether, 2-butoxyethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ... Ethylene glycol dimethyl ether, 1-methoxy-2-propyl acetate, 2-ethoxyethyl acetate, 1,2-dimethoxyethane ethyl acetate, cellosolve acetate, methyl lactate, ethyl lactate, n-butyl acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, gamma-butyrolactone, dimethyl sulfoxide, dimethylformamide, tetraethylene glycol, tetrahydrofurfuryl alcohol, N-methyl-2-pyrrolidone, 1,4-dioxane, methanol, ethanol, 1-propanol, 2-propanol and butanol.

[0101] Non-limiting examples of aqueous developers include solutions of tetramethylammonium hydroxide, potassium hydroxide, sodium carbonate, and hydrochloric acid in water.

[0102] Alternatively, the pattern in the film containing RMU can be directly produced by ablation using a laser source with a wavelength below 450nm. In this case, the absorbance of the composition needs to be sufficient to directly absorb at the operating wavelength of the light. The required absorbance depends on multiple parameters, such as wavelength and fluence.

[0103] Non-limiting examples of etching used to transfer the pattern are dry etching and wet etching. Etching can be performed in a single step or in multiple steps.

[0104] Dry etching can be to remove material physically by plasma, to remove material chemically by gas, or to remove physically and chemically (referred to as reactive ion etching (RIE)). Dry etching can include one or more gases, one or more reactive ions, one or more plasmas or combinations thereof, which are sufficient to etch or remove the material of the underlying substrate at an etching rate faster than that of the refined metal-containing three-dimensional layer. Non-limiting examples of reactants used in dry etching are selected from oxygen, nitrogen, ammonia, hydrofluoric acid and halogenated gases (e.g., CHF3 (trifluoromethane), CF4 (tetrafluoromethane), C4F8 (octafluorocyclobutane), Cl2 (chlorine), SF6 (sulfur hexafluoride) and BCl3 (boron trichloride)) alone or in combination. Dry etching includes gases in plasma and inductively coupled plasma (ICP) conditions.

[0105] Wet etching involves contact with a liquid that selectively removes the material or substrate. Non-limiting examples of reactants used in wet etching processes include alkalis, inorganic or organic acids, and organic solvents. These reactants can be used alone or in combination. For example, the alkali or inorganic acid can be diluted with an organic solvent, such as dimethyl sulfoxide, n-methyl pyrrolidone, tetrahydrofurfuryl alcohol, etc. The reactants can be heated at room temperature.

[0106] The type of etch used, the type of reactants used and the number of etching steps used depend on the nature of the layers and the composition of the substrate involved.

[0107] A schematic depiction of the method is shown in Figure 1 Reference Figure 1 , the substrate 100 includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. The composition containing RMU is applied to the substrate in the form of a thin film and heated to remove any residual solvent or volatiles. After being exposed to a light source through a mask, a photomask or a mold, the unexposed portion of the film containing RMU is removed with a developer to obtain a patterned film 101 containing RMU. The pattern is transferred to the substrate 100 below by dry etching or wet etching technology. A patterned substrate 102 is obtained. Any remaining film containing RMU can be removed by any etching technology.

[0108] A schematic depiction of this approach is shown in Figure 2 Reference Figure 2, the substrate 200 includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. The organic layer 201 is applied to the substrate in the form of a thin film. The organic layer film is made insoluble in an organic solvent or an aqueous developer by being subjected to heat or light. The composition containing RMU is deposited on top of the organic layer in the form of a thin film. The film containing RMU is heated to remove any residual solvent or volatiles. After being exposed to a light source through a mask, a photomask or a mold, the unexposed portion of the film containing RMU is removed with a developer to obtain a patterned film 202 containing RMU. The pattern from the film 202 containing RMU is further transferred to the organic layer 201 below by dry etching or wet etching technology. A patterned organic layer 203 is obtained. Any remaining film containing RMU can be removed by any etching technology. The pattern from the patterned organic layer 203 is further transferred to the substrate 200 below by dry etching or wet etching technology. A patterned substrate 204 is obtained. Any remaining organic layers may be removed by any etching technique.

[0109] The organic layer 201 is any film-forming composition. The criteria for selecting such an organic layer are based on its relative etching selectivity with the film containing the RMU and the underlying substrate. The organic layer may also be used for other purposes, such as controlling light reflection from the underlying substrate and providing a conformal or planarized coating to cover any contours present in the underlying substrate. The film thickness of the organic layer is between about 5 nm and about 500 microns. A non-limiting example of an organic layer is a film containing cross-linked polyhydroxystyrene.

[0110] Alternatively, a pattern in a film containing RMU may be produced by a method comprising 1) providing a photoresist; 2) depositing the photoresist on a film containing RMU; 3) drying the photoresist at a temperature below 200° C.; 4) forming a pattern in the photoresist film; and 5) transferring the pattern to a film containing RMU by etching.

[0111] Prior to step 1, the film comprising RMU is made insoluble in an organic solvent or an aqueous developer by subjecting the film to heat or light.

[0112] The photoresist provided can be positive, or negative. The photoresist depends on the type of radiation source. The non-limiting examples of photoresist include novolac, polyhydroxystyrene, acrylic, PMMA, epoxy resin, cycloolefin, fluoropolymer, silsesquioxane, polybenzoxazole and polyimide-based platform. The photoresist can be deposited on the film comprising RMU by any conventional method. The non-limiting examples of coating methods are spin coating, spray coating, dip coating, scraper or scraping, slot die coating, lamination and dry film lamination.

[0113] In an embodiment, a drying photoresist is used to drive off any organic solvent or other volatile material to form a uniform defect-free film. An example of drying a photoresist is heating the substrate at a temperature in the range of about 40° C. to 200° C. for a few seconds to a few minutes. Typical film thicknesses of photoresists are between about 5 nm and about 500 microns.

[0114] The pattern in the photoresist film can be formed by exposing the photoresist film to a radiation source through a mask, a photomask or a mold. Exposure can also be performed by direct writing. In the case of a positive photoresist, the exposed portion of the photoresist film is removed by a developer. In the case of a negative photoresist, the unexposed portion of the photoresist film is removed by a developer. Non-limiting examples of developers are organic solvents and aqueous solutions of tetramethylammonium hydroxide.

[0115] The pattern from the photoresist film is transferred to the film containing the RMU by etching. Non-limiting examples of etching used for transferring the pattern are the above-mentioned dry etching and wet etching. Etching can be performed in a single step or in multiple steps.

[0116] A schematic depiction of this approach is shown in Figure 3 Reference Figure 3 , substrate 300 includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. A composition containing RMU is applied to the substrate below in the form of a film 301. The film containing RMU is heated or exposed to a light source so that the film is insoluble in an organic solvent or an aqueous developer. A photoresist film 302 is applied on top of the film containing RMU. After heating to remove any residual solvent or volatiles, the photoresist film is exposed to a light source through a mask, a photomask or a mold. The exposed portion of the photoresist film (positive) or the unexposed portion of the photoresist film (negative) is removed with a developer to obtain a patterned photoresist film 303. The pattern from the photoresist film 303 is transferred to the film 301 containing RMU by dry etching or wet etching techniques. A patterned film 304 containing RMU is obtained. Any residual photoresist layer can be removed by any etching technique. The pattern from the RMU-containing patterned film 304 is further transferred to the underlying substrate 300 by dry etching or wet etching techniques. The result is a patterned substrate 305. Any remaining RMU-containing film may be removed by any etching technique.

[0117] A schematic depiction of this approach is shown in Figure 4 Reference Figure 4, the substrate 400 includes at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. An organic lower layer 401 is applied to the substrate. The organic layer is made insoluble in an organic solvent or an aqueous developer by undergoing a step of heating or exposure to a light source. A composition 402 containing RMU is applied to the substrate below in the form of a film. The film 402 containing RMU is made insoluble in an organic solvent or an aqueous developer by undergoing heat or exposure to a light source. A photoresist film 403 is applied to the film containing RMU below. The photoresist film is heated to remove residual solvent or volatiles. The photoresist film is exposed to a light source through a mask, a photomask or a mold. The exposed portion of the film (positive) or the unexposed portion of the film (negative) is removed with a developer to obtain a patterned photoresist film 404. The pattern from the patterned photoresist film 404 is transferred to the film containing RMU below 402 by dry etching or wet etching technology. A patterned film 405 containing RMU is obtained. Any remaining photoresist film can be removed by any etching technique. In a subsequent step, the pattern from the patterned film 405 containing RMU is further transferred to the underlying organic layer 401 by etching. A patterned organic layer 406 is obtained. Any remaining film 405 containing RMU can be removed by any etching technique. Next, the pattern from the patterned organic layer 406 is transferred to the substrate 400 by dry etching or wet etching technology. A patterned substrate 407 is obtained. Any residual organic layer can be removed by any etching technique.

[0118] In another embodiment, the present invention provides a method for forming a doped patterned substrate. The method comprises a) providing RMU; b) preparing a composition comprising RMU; c) providing a substrate; d) depositing the composition on the substrate; e) drying the composition at a temperature below 200° C.; f) forming a pattern in a film comprising RMU; and g) depositing a dopant into the exposed portion of the substrate using a reactive ion beam.

[0119] The RMU, the composition comprising the RMU and the substrate are as described above. The deposition and drying steps are as described above. The pattern in the film comprising the RMU can be formed by any of the above methods.

[0120] Ion implantation introduces dopants to the exposed underlying substrate via a reactive ion beam. Non-limiting examples of dopants used are ions of phosphorus, boron, arsenic, antimony, aluminum, gallium, and indium. Non-limiting examples of the underlying substrate are silicon carbide.

[0121] The doped substrate with the patterned film including RMU may be further baked or annealed before or after removing the patterned film. Typical baking temperatures are about 200°C to about 1400°C.

[0122] The remaining RMU-containing film may be removed by dry or wet etching, for example, by using a 5% hydrofluoric acid solution to remove the remaining RMU-containing film.

[0123] No dopant is present on the substrate beneath the patterned portion of the RMU-containing film.

[0124] A schematic depiction of this approach is shown in Figure 5 Reference Figure 5 , providing a substrate 500 including at least one element selected from Si, O, N, Al, Cu, C, Ga, Ge, As, Zn and W, alone or in combination. Applying a composition containing RMU to a substrate in the form of a film. Heating the film containing RMU to remove any residual solvent or volatiles. After exposure to a light source through a mask, a photomask or a mold, removing the unexposed portion of the film containing RMU with a developer to produce a patterned film 501 containing RMU. The reactive ion beam deposits dopants into the region of the substrate 500 not covered by the patterned film 501 containing RMU with energy sufficient to penetrate the substrate, forming a doped region 502 of the substrate. Obtaining a doped substrate 505. The remaining portion of the film containing RMU can be removed by any etching technique. Example

[0125] The following examples demonstrate reduced yield impurities in the refined metal-containing compounds.

[0126] Yield Impurity Analysis: 2 g RMU solid or solution samples were analyzed for metal levels in ppb by ICP-MS or GFAA.

[0127] Comparative Example 1

[0128] Yield impurity analysis of zirconium carboxyethyl acrylate (60 wt% in isopropanol) contained 2,060,000 ppb or 0.2% sodium, 27,000 ppb potassium, 847,000 ppb aluminum, 2,600 ppb iron, and 2,800 ppb zinc.

[0129] Example 1

[0130] To a stirred solution of deionized water (500 mL) adjusted to pH 4 with acrylic acid in a 1 L polypropylene beaker was added a solution of zirconium acrylate (50 g, 20% by weight in methanol) dropwise. The zirconium acrylate precipitate was isolated by vacuum filtration on a 1-L filter bottle using 11 micron filter paper with a polypropylene Buchner funnel under vacuum (400 mbar). The precipitate was dried in a 10 mbar vacuum oven at 70°C for 2 hours.

[0131] In this example, the process reduced the yield impurities in the zirconium acrylate to 1,100 ppb sodium and 700 ppb iron.

[0132] Example 2

[0133] A solution of hafnium carboxyethyl acrylate (20 g, 60% by weight in 1-butanol) was filtered through a 1.0 micron PTFE syringe filter and then added dropwise to a stirred solution of deionized water (200 mL) adjusted to pH 4 with 2-carboxyethyl acrylate in a 600 mL polypropylene beaker. The hafnium carboxyethyl acrylate precipitate was isolated by allowing the precipitate to settle and then decanting the aqueous liquid. The precipitate was dissolved in 1-methoxy-2-propanol (40% by weight) and distilled at 60° C. under a vacuum of 10 mbar until the solution was 60% by weight.

[0134] In this example, the process reduces the yield impurities in the hafnium carboxyethyl acrylate to 50% of the initial sodium content, 65% of the initial iron content, and 40% of the initial copper content.

[0135] Example 3

[0136] A solution of zirconium carboxyethyl acrylate (200 g, 60% by weight in 1-propanol) was filtered through 8.0 micron filter paper and then added dropwise to a stirred solution of deionized water (2000 mL) adjusted to pH 4 with 2-carboxyethyl acrylate in a 4 L polypropylene beaker. The zirconium carboxyethyl acrylate precipitate was isolated by allowing the precipitate to settle and then decanting the liquid portion containing acidified deionized water. The precipitate was dried in a 10 mbar vacuum oven at 60°C for 2 hours.

[0137] In this example, the process reduced the yield impurities in zirconium carboxyethyl acrylate to 900 ppb sodium, 750 ppb iron, and 170 ppb copper.

[0138] Example 4

[0139] A solution of zirconium carboxyethyl acrylate (100 g, 60% by weight in 1-butanol) was dissolved in 1-butanol (300 g). Deionized water (100 g) adjusted to pH 4 with 2-carboxyethyl acrylate was added and the mixture was stirred for 20 minutes. After the two phases were separated, the aqueous phase (75 g) was removed. The organic phase was distilled at 60° C. under a vacuum of 10 mbar until the solution was 60% by weight in 1-butanol. The zirconium carboxyethyl acrylate solution was filtered through a 1.0 micron PTFE membrane filter.

[0140] In this example, the process reduced the yield impurities in zirconium carboxyethyl acrylate to 85% of the initial sodium content and 60% of the initial iron content.

[0141] Example 5

[0142] A solution of hafnium carboxyethyl acrylate (100 g, 60% by weight in 1-butanol) was dissolved in 1-butanol and ethyl acetate (300 g). Deionized water (100 g) adjusted to pH 4 with 2-carboxyethyl acrylate was added and the mixture was stirred for 20 minutes. After the two phases were separated, the aqueous phase (75 g) was removed. The organic phase was distilled at 40-60° C. under a vacuum of 10 mbar until the solution was 60% by weight in 1-butanol.

[0143] In this example, the process reduced the yield impurities in hafnium carboxyethyl acrylate to 1,200 ppb sodium, 960 ppb potassium, 4,800 ppb copper, 1,200 ppb calcium, 1,680 ppb iron, 120 ppb zinc, and no detectable amounts of chromium, magnesium, or manganese.

[0144] Example 6

[0145] The refined carboxyethyl zirconium acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 purchased from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 purchased from Ciba Specialty Chemicals). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 0.1 micron PTFE syringe filter.

[0146] A 100 mm silicon wafer having a 380 nm thick silicon oxide layer on the polished side was used as the substrate. The composition comprising refined zirconium carboxyethyl acrylate was spin coated on the silicon oxide layer. The composition comprising refined zirconium carboxyethyl acrylate was dried at 100° C. for 60 seconds and the film thickness was measured at 200 nm. The film comprising refined zirconium carboxyethyl acrylate was exposed through a contact photomask on a Karl Suss MJB3 broadband mask aligner. The unexposed areas of the film comprising refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0147] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer coated with silicon oxide to form a thin film, the film is dried at a temperature below 200° C., and exposed to a light source through a mask. The patterned film comprising refined zirconium carboxyethyl acrylate is developed with an organic solvent developer. A 5 micron pattern resolution is produced.

[0148] Example 7

[0149] A portion of the wafer containing the patterned film of refined zirconium carboxyethyl acrylate described in Example 6 was etched using a combination of C4F8 and O2 reactive ion etching (RIE) gases to remove the exposed underlying silicon oxide layer. The etch rate of the refined zirconium carboxyethyl acrylate film was 0.58 nm / s, and the etch rate of the exposed underlying silicon oxide layer was 2.58 nm / s.

[0150] In this example, a patterned silicon oxide substrate was formed by transferring the pattern in the thin film containing refined zirconium carboxyethyl acrylate in Example 6 by dry etching.

[0151] Example 8

[0152] Another portion of the wafer containing the patterned film of refined zirconium carboxyethyl acrylate described in Example 6 was baked at 250° C. for 5 minutes before removing the exposed underlying silicon oxide layer using a combination of C4F8 and O2RIE gas plasma etching. The etch rate of the film containing refined zirconium carboxyethyl acrylate was 0.00 nm / s, and the etch rate of the exposed underlying silicon oxide was 2.58 nm / s.

[0153] In this example, a patterned silicon oxide substrate was formed by first heating the patterned film containing purified zirconium carboxyethyl acrylate of Example 6 and then transferring the pattern by dry etching. The etching rate of the film containing purified zirconium carboxyethyl acrylate was further reduced.

[0154] Example 9

[0155] The refined zirconium carboxyethyl acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol and 1-methoxy-2-propyl acetate. A photoinitiator was added to the solution (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, Irgacure 819, purchased from Ciba Specialty Chemicals). The resulting mixture was homogenous after stirring. The homogenous solution was filtered through a 0.2 micron PTFE syringe filter. The composition containing refined zirconium carboxyethyl acrylate was spin coated on a 50 mm silicon wafer substrate. The composition containing refined zirconium carboxyethyl acrylate was dried at 90° C. for 120 seconds and the film thickness was determined to be 150 nm. The film containing refined zirconium carboxyethyl acrylate was exposed with a Raith electron beam writer 10 keV tool at an exposure dose of 0.22 pC. The unexposed areas of the film containing refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0156] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer to form a film, the film is dried at a temperature below 200°C, and exposed to a direct write electron beam source. The patterned film comprising refined zirconium carboxyethyl acrylate is developed with an organic solvent developer. A 250nm pattern resolution is formed by direct writing.

[0157] Example 10

[0158] The refined zirconium carboxyethyl acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol and 1-methoxy-2-propyl acetate. The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 0.2 micron PTFE syringe filter. The composition containing the refined zirconium carboxyethyl acrylate was spin-coated on a 50 mm silicon wafer substrate. The composition containing the refined zirconium carboxyethyl acrylate was dried at 90° C. for 120 seconds, and the film thickness was determined to be 150 nm. The film containing the refined zirconium carboxyethyl acrylate was exposed with a Raith electron beam writer 10 keV tool at an exposure dose of 0.22 pC. The unexposed areas of the film containing the refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0159] In this example, refined zirconium carboxyethyl acrylate is provided and prepared as a composition without an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer to form a film, the film is dried at a temperature below 200°C, and exposed to a direct write electron beam source. The patterned film comprising refined zirconium carboxyethyl acrylate is developed with an organic solvent developer. A 250 nm pattern resolution is formed by direct writing.

[0160] Embodiment 11

[0161] The refined carboxyethyl zirconium acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol and 1-methoxy-2-propyl acetate. A photoinitiator was added to the solution (2,4,6-trimethylbenzoyldiphenylphosphine oxide, Lucerin TPO, purchased from BASF). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 1.0 micron PTFE syringe filter.

[0162] The composition containing refined zirconium carboxyethyl acrylate was spin coated on a 100 mm silicon wafer substrate. The composition containing refined zirconium carboxyethyl acrylate was dried at 100° C. for 60 seconds and the film thickness was measured at 100 nm. The film containing refined zirconium carboxyethyl acrylate was exposed with a 405 nm direct write laser filtered to 10%. The unexposed areas of the film containing refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0163] In this embodiment, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer to form a film, the film is dried at a temperature below 200° C., and exposed to a direct write light source. The patterned film comprising refined zirconium carboxyethyl acrylate is developed with an organic solvent developer. A 600 nm pattern resolution is formed by direct writing.

[0164] Example 12

[0165] The refined carboxyethyl zirconium acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 purchased from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 purchased from Ciba Specialty Chemicals). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 0.2 micron PTFE syringe filter.

[0166] A 100 mm silicon wafer was used as a substrate. A composition containing refined zirconium carboxyethyl acrylate was spin-coated on the substrate. The composition containing refined zirconium carboxyethyl acrylate was dried at 110° C. for 60 seconds, and the film thickness was measured at 500 nm. A laser with a fluence of 250 mJ / cm2 and a frequency of 100 Hz at a wavelength of 308 nm was used in the mirror scanning processing method.

[0167] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition containing refined zirconium carboxyethyl acrylate is deposited on a silicon wafer to form a thin film, and the film is dried at a temperature below 200° C. and exposed to a heat source. Then, the thin film containing refined zirconium carboxyethyl acrylate is patterned by laser ablation using a mask to obtain a 5 micron pattern resolution.

[0168] Example 13

[0169] The refined carboxyethyl zirconium acrylate described in Example 4 was dissolved in a solvent combination of 1-methoxy-2-propanol, n-propanol, and 1-methoxy-2-propyl acetate. A thermal initiator was added to the solution (benzoyl peroxide purchased from Sigma-Aldrich). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 0.1 micron PTFE syringe filter.

[0170] A 300 mm silicon wafer with a 200 nm thick silicon oxide layer on the polished side was used as a substrate. A bottom anti-reflective coating similar to the coating described in Reichmanis, E. and Thompson, LF "Polymer materials for microlithography" Chem. Rev. Vol. 89, 1989, pp. 1273-1289 was spin-coated as an organic layer on the silicon oxide side, dried and cross-linked, and the film thickness was measured at 130 nm. A composition comprising refined zirconium carboxyethyl acrylate was spin-coated on top of the organic layer. For a 30 nm film thickness, the film comprising refined zirconium carboxyethyl acrylate was dried at 120° C. and then baked at 225° C. The dielectric constant of the film comprising RMU was measured by a mercury probe at 1 MHz. The dielectric constant was measured to be 11.76 (series) and 11.75 (parallel). A negative tone immersion photoresist sensitive to 193 nm light similar to the photoresist described in Sanders, DP "Advances in patterning materials for 193 nm immersion lithography" Chem. Rev., Vol. 110, 2010, pp. 312-360 was spin coated on top of the film containing refined zirconium carboxyethyl acrylate. The photoresist was dried to a film thickness of 75 nm and exposed under 193 nm immersion conditions before developing the unexposed areas with n-butyl acetate.

[0171] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited to form a thin film on a silicon wafer covered with an organic layer, the film is dried at a temperature below 200° C., and exposed to a heat source at a temperature below 1400° C. A photoresist is provided and deposited on the film comprising refined zirconium carboxyethyl acrylate. The photoresist is exposed to a light source and developed with an aqueous developer. A 50 nm pattern resolution is produced.

[0172] Embodiment 14

[0173] The exposed underlying film comprising refined zirconium carboxyethyl acrylate described in Example 13 was etched using a combination of CHF3 and O2 RIE gases (45 sccm and 5 sccm, respectively, 40 mTorr, 150 W). The etch rate of the exposed underlying film comprising refined zirconium carboxyethyl acrylate was 0.17 nm / s, and the etch rate of the patterned photoresist film was 0.00 nm / s.

[0174] The exposed underlying organic layer was etched using O2 RIE gas (10 sccm, 10 mTorr, 50 W). The etch rate of the exposed underlying organic layer was 0.70 nm / s, the etch rate of the patterned photoresist film was 0.75 nm / s, and the etch rate of the exposed film containing refined zirconium carboxyethyl acrylate was 0.03 nm / s.

[0175] The exposed underlying silicon oxide layer was etched with a combination of C4F8 and O2 RIE gases (45 sccm and 5 sccm, respectively, 10 mTorr, 29 W, using ICP 3500 W). The etch rate of the exposed underlying silicon oxide layer was 2.58 nm / s. The etch rate of the patterned film containing RMU was 0.58 nm / s. Any trace organic layer was removed by etching with O2 RIE gas.

[0176] In this example, the pattern in the photoresist of Example 13 was transferred by dry etching into a thin film comprising purified zirconium carboxyethyl acrylate, which was then dry etched into an organic layer to form a patterned organic layer on top of a substrate. The pattern was dry etched into the silicon oxide layer of the substrate.

[0177] Embodiment 15

[0178] The refined zirconium carboxyethyl acrylate described in Example 3 was dissolved in a solvent combination of 1-methoxy-2-propanol, n-propanol, and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 from Ciba Specialty Chemicals). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 0.2 micron PTFE syringe filter.

[0179] The composition containing refined zirconium carboxyethyl acrylate was spin coated on a 100 mm quartz wafer substrate. The composition containing RMU was dried at 110° C. and the film thickness was measured at 440 nm. The film containing refined zirconium carboxyethyl acrylate was exposed through a contact photomask on a Karl Suss MJB3 mask aligner. Unexposed areas of the film containing refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0180] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a quartz wafer to form a film, the film is dried at a temperature below 200° C., and exposed to a light source through a mask. The patterned film comprising RMU is developed with 1-methoxy-2-propanol. A 1-inch pattern resolution is produced.

[0181] Example 16

[0182] At 190keV, 150μA, 5.00 x 10 1531 P+ ions / cm 2 The exposed underlying quartz wafer and the patterned film comprising refined zirconium carboxyethyl acrylate described in Example 15 were injected. The patterned film comprising refined zirconium carboxyethyl acrylate did not break or dissipate during the injection, indicating no damage caused by penetration of dopant ions. The patterned film comprising refined zirconium carboxyethyl acrylate was removed by a mineral acid. The area of ​​the quartz wafer previously covered by the patterned film comprising refined zirconium carboxyethyl acrylate was analyzed by an EDX detector, and no phosphorus was detected, indicating no dopant penetrated the quartz wafer.

[0183] In this example, dopants are deposited by ion implantation through the pattern in the thin film containing RMU of Example 15 to form a doped patterned quartz wafer.

[0184] Embodiment 17

[0185] The refined carboxyethyl zirconium acrylate described in Example 3 was dissolved in a solvent combination of 1-methoxy-2-propanol, n-propanol, and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 from Ciba Specialty Chemicals). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 1.0 micron PTFE syringe filter.

[0186] The composition comprising zirconium carboxyethyl acrylate was spin coated on a 100 mm silicon wafer substrate. The composition comprising zirconium carboxyethyl acrylate was dried at 110° C. and the film thickness was measured at 690 nm. The film comprising zirconium carboxyethyl acrylate was exposed through a contact photomask on a Karl Suss MJB3 mask aligner. Unexposed areas of the film comprising zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0187] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer substrate to form a film, the film is dried at a temperature below 200° C., and exposed to a light source through a mask. The patterned film comprising refined zirconium carboxyethyl acrylate is developed using 1-methoxy-2-propanol. A 1-inch pattern resolution is produced.

[0188] Embodiment 18

[0189] The patterned film containing purified carboxyethyl zirconium acrylate described in Example 17 was baked at 250°C for 20 minutes. 1531 P+ ions / cm 2 The exposed underlying silicon wafer and the patterned film comprising zirconium carboxyethyl acrylate were implanted. The patterned film comprising zirconium carboxyethyl acrylate did not crack or dissipate during implantation, indicating that no dopant penetrated into the silicon wafer area previously covered by the film comprising zirconium carboxyethyl acrylate. The sample was then baked at 400° C. for 10 minutes, and the patterned film comprising zirconium carboxyethyl acrylate was removed from the patterned doped silicon wafer using a buffered oxide etching solution.

[0190] In this embodiment, the ion implantation 31 P + Ions permeated the pattern in the thin film containing purified zirconium carboxyethyl acrylate of Example 17 to form a doped patterned silicon wafer. The residual thin film containing purified zirconium carboxyethyl acrylate was removed by wet etching. The substrate was undoped in the area previously covered by the thin film containing purified zirconium carboxyethyl acrylate.

[0191] Embodiment 19

[0192] The refined carboxyethyl zirconium acrylate described in Example 3 was dissolved in a solvent combination of 1-methoxy-2-propanol, n-propanol, and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 from Ciba Specialty Chemicals). The resulting mixture was homogeneous after stirring. The homogeneous solution was filtered through a 1.0 micron PTFE syringe filter.

[0193] The composition comprising refined zirconium carboxyethyl acrylate was spin coated on a 100 mm silicon wafer substrate. The composition comprising refined zirconium carboxyethyl acrylate was dried at 110° C. and the film thickness was measured at 580 nm. The film comprising refined zirconium carboxyethyl acrylate was exposed through a contact photomask on a Karl Suss MJB3 mask aligner. Unexposed areas of the film comprising refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0194] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a silicon wafer to form a film, the film is dried at a temperature below 200° C., and exposed to a light source through a mask. The patterned film comprising RMU is developed with 1-methoxy-2-propanol. A 1-inch pattern resolution is produced.

[0195] Embodiment 20

[0196] The patterned film containing purified carboxyethyl zirconium acrylate described in Example 19 was baked at 600°C for 5 minutes. The film was heated at 150 keV, 250 μA on a heating stage at 650°C with 5.00 x 10 1627 Al + ions / cm 2 The exposed underlying silicon wafer and the patterned film comprising refined zirconium carboxyethyl acrylate were implanted. The patterned film comprising refined zirconium carboxyethyl acrylate did not crack or dissipate during implantation, indicating that no dopant penetrated into the area of ​​the silicon wafer previously covered by the film comprising refined zirconium carboxyethyl acrylate.

[0197] In this example, dopant was deposited by ion implantation through the pattern in the thin film comprising zirconium carboxyethyl acrylate of Example 19 to form a doped patterned silicon wafer. The residual thin film comprising zirconium carboxyethyl acrylate was removed by wet etching. The substrate was undoped in the areas previously covered by the thin film comprising zirconium carboxyethyl acrylate.

[0198] Embodiment 21

[0199] The refined carboxyethyl zirconium acrylate described in Example 3 was mixed with acryl-terminated POSS (43% by weight carboxyethyl zirconium acrylate) and then dissolved in a solvent combination of 1-methoxy-2-propanol, n-propanol, and 1-methoxy-2-propyl acetate. Photoinitiators were added to the solution (1-hydroxycyclohexyl-phenyl ketone Irgacure 184 from Ciba Specialty Chemicals, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide Irgacure 819 from Ciba Specialty Chemicals). The resulting mixture was homogenous after stirring. The homogenous solution was filtered through a 0.2 micron PTFE syringe filter.

[0200] The composition containing refined zirconium carboxyethyl acrylate was spin coated on a 100 mm quartz wafer substrate. The composition containing RMU was dried at 110° C. and the film thickness was measured at 710 nm. The film containing refined zirconium carboxyethyl acrylate was exposed through a contact photomask on a Karl Suss MJB3 mask aligner. The unexposed areas of the film containing refined zirconium carboxyethyl acrylate were developed with 1-methoxy-2-propanol.

[0201] In this example, refined zirconium carboxyethyl acrylate is provided and prepared into a composition by mixing with an initiator. The composition comprising refined zirconium carboxyethyl acrylate is deposited on a quartz wafer to form a film, the film is dried at a temperature below 200° C., and exposed to a light source through a mask. The patterned film comprising RMU is developed with 1-methoxy-2-propanol. A 1-inch pattern resolution is produced.

[0202] Embodiment 22

[0203] The exposed underlying substrate and the patterned film containing purified carboxyethyl acrylate zirconium and acryl-terminated POSS described in Example 21 were baked at 250°C for 20 minutes. 1531 P+ ions / cm 2 The exposed underlying silicon wafer and the patterned film comprising refined zirconium carboxyethyl acrylate and acryl-terminated POSS were injected. The patterned film comprising refined zirconium carboxyethyl acrylate and acryl-terminated POSS did not crack or dissipate during the injection, indicating that there was no damage caused by the penetration of dopants into the silicon wafer area previously covered by the film comprising refined zirconium carboxyethyl acrylate and acryl-terminated POSS.

[0204] In this embodiment, dopants are deposited by ion implantation through the pattern in the thin film comprising RMU and PU of Example 21 to form a doped patterned silicon wafer.

[0205] Variations of the above disclosed products, methods and systems may be combined with other systems as desired. In addition, those skilled in the art may subsequently make currently unforeseen or unanticipated substitutions, modifications and improvements, which are also encompassed by the claims.

Claims

1. A method of forming a refined metalliferous unit (RMU), the method comprising: a. Provide Metal Unit (MU) Where MU is represented by structure I: MA w B x C y Structure I wherein M comprises a metal having a formal valence of 0-7 and comprises at least one metal selected from the group consisting of Zr, Hf, Ge, Ti, Nb, Pb, Gd, Sn, Ce, Eu, In, Nd, Sb, Ga, Se, Cd, Ta, Co, Pt, Au, W, V, Tl, Te, Sr, Sm, La, Er, Pd, In, Ba, As and Y; ligand A comprises a reactive functional group capable of undergoing a chemical reaction; w is 0 to 7; ligands B and C are selected, alone or in combination, from: oxygen, nitrogen, sulfur or a halogen atom; hydroxyl, peroxide, phosphate, borate, tungstate, sulfate, silicate; substituted or unsubstituted linear, branched or cyclic alkyl, alkyl ether, alkyl ester, sulfanyl, alkenyl or alkynyl; substituted or unsubstituted aryl; and -XR 1 , wherein X represents an organic functional group selected from oxy, sulfo, carboxyl, thiocarboxyl, sulfo, oxalate, acetylacetonate, carbanion, carbonyl, thiocarbonyl, cyano, nitro, nitrite, nitrate, nitrosyl, azide, cyano, isocyano, thiocyano, isothiocyano, amide, amine, diamine, arsenic, biarsenic, phosphine and diphosphine, and R 1 represents a hydrogen atom, a substituted or unsubstituted straight chain, branched chain or cyclic alkyl or sulfanyl group, a heterocyclic group, an alicyclic group, and a substituted or unsubstituted aryl or heteroaryl group; x and y are 0 to 7, and w+x+y is 2-7; and MU is dissolved in an organic solvent, MU being present in an amount of about 5 weight % to about 70 weight % based on the total weight of MU and the organic solvent to form a MU solution, b. acidifying the solution in deionized water to provide a pH of 2 to 6.5 by adding an acid to the deionized water, the acid being selected from acrylic acid and 2-carboxyethyl acrylate, and c. mixing the MU solution with an acidified solution of deionized water, and d. Separate the RMU, wherein the separated RMU contains yield impurities, and the amount of each yield impurity in the separated RMU is less than 5000 ppb based on the total weight of the RMU, The metal-containing unit comprises at least one member selected from zirconium (meth)acrylate, zirconium carboxyethyl acrylate, hafnium (meth)acrylate, hafnium carboxyethyl acrylate, titanium (meth)acrylate, titanium carboxyethyl acrylate, tantalum (meth)acrylate, tantalum carboxyethyl acrylate, niobium (meth)acrylate and niobium carboxyethyl acrylate.

2. The process of claim 1, wherein MU is dissolved in a water-miscible organic solvent and RMU is precipitated during step d.

3. The method of claim 2, wherein the water-miscible solvent is selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, tert-butanol, 1-methoxy-2-propanol, 2-propoxyethanol, 2-butoxyethanol, 2-ethoxyethyl ether, 2-butoxyethyl ether, dimethyl sulfoxide, γ-butyrolactone, acetonitrile, ethyl lactate, N-methylpyrrolidone, dimethylformamide, tetrahydrofurfuryl alcohol, tetrahydrofuran and acetone, alone or in combination.

4. The method of claim 1, wherein the organic solvent is a water-immiscible solvent, the method further comprising: f. separating the acidified solution of deionized water and the MU solution into different layers after step d of claim 1, and g. Discard the layer containing the deionized water acidified solution and separate the layer containing the RMU solution.

5. The method of claim 4, wherein the water-immiscible organic solvent is selected from the group consisting of ethyl acetate, propyl acetate, butyl acetate, 1-methoxy-2-propyl acetate, n-butanol, 4-methyl-2-pentanol, hexane, heptane, toluene, 2-methyltetrahydrofuran, 2-butanone, 4-methyl-2-pentanone, 2-heptanone, cyclohexanone, methyl tert-butyl ether and cyclopentyl methyl ether, alone or in combination.

6. A method for forming a patterned substrate, the method comprising: a. providing a refined metal-containing unit (RMU) by the method of claim 1, b. preparing a composition comprising the RMU; c. providing a substrate, d. depositing the composition comprising RMU on a substrate to form a thin film, e. drying the film containing RMU at a temperature of less than 200°C, f. forming a pattern in a film comprising RMU, and g. Transfer the pattern to the substrate, The separated RMU contains yield impurities, and the amount of each yield impurity in the separated RMU is less than 5000 ppb based on the total weight of the RMU.

7. The method of claim 6, wherein step (b) further comprises incorporating a catalyst or initiator capable of inducing a reaction of the reactive functional groups of the refined metal-containing unit.

8. The method of claim 6, wherein step (b) further comprises incorporating into the composition a prepolymer unit PU containing at least two reactive functional groups.

9. The method of claim 6, wherein step (b) further comprises incorporating into the composition nanoparticles comprising surface treated or untreated silicon oxide, titanium oxide, zirconium oxide, hafnium oxide, CdSe, CdS, CdTe, lanthanum oxide, niobium oxide, tungsten oxide and strontium oxide, alone or in combination.

10. The method of claim 6, wherein step (b) further comprises incorporating into the composition a comonomer having only one reactive functional group.

11. The method of claim 6, wherein step (b) further comprises incorporating an adhesion promoter into the composition.

12. The method of claim 6, wherein step (b) further comprises incorporating into the composition at least one of a colorant and a dye.

13. The method of claim 6, wherein the substrate comprises at least one element selected from the group consisting of silicon, oxygen, nitrogen, aluminum, copper, carbon, tungsten, germanium, gallium, and arsenic.

14. The method of claim 6, wherein the film comprising RMU is sandwiched between a patterned photoresist and a substrate.

15. The method of claim 14, wherein the pattern from the photoresist is transferred to the thin film containing the RMU by etching.

16. The method of claim 15, wherein the pattern from the thin film comprising the RMU is transferred to the substrate by etching.

17. The method of claim 6, wherein the pattern in the film comprising RMU is produced as follows: h. exposing the film containing the RMU to a source of actinic radiation through a mask or mold or reticle, and i. developing the unexposed portions of the film with a developer.

18. The method of claim 17, wherein the source of actinic radiation is selected from the group consisting of light, electron beam, and heat, alone or in combination.

19. The method of claim 17, wherein the patterned film comprising RMU is produced by direct writing with an excimer laser source or an electron beam.

20. The method of claim 6, wherein the pattern from the RMU-containing film is transferred to the substrate by etching.

21. The method of claim 6, further comprising: j. Forming an organic layer between the RMU-containing film and the substrate.

22. The method of claim 21, wherein the pattern is transferred from the thin film containing the RMU to the organic layer by etching.

23. The method of claim 22, wherein the pattern is transferred from the organic layer to the substrate by etching.

24. The method of claim 6, wherein the substrate is doped through a patterned thin film comprising RMU by a method comprising: k. depositing dopants on the substrate using a reactive ion beam, and l. Remove the patterned film containing the RMU.

25. The method of claim 24, wherein the pattern in the film containing the RMU is generated by pattern transfer from a patterned photoresist film by etching.

26. The method of any one of claims 15, 16, 20, 22, 23 and 25, wherein the etching process comprises dry etching.

27. The method of any one of claims 15, 16, 20, 22, 23 and 25, wherein the etching process comprises wet etching.

28. A patterned substrate formed by the method of any one of claims 6, 16, 20 and 23.

29. A doped substrate formed by the method of claim 24.

30. An electronic device comprising the patterned substrate of claim 28.

31. An electronic device comprising the doped substrate of claim 29.

32. The method of claim 13, wherein the substrate comprises at least one member selected from the group consisting of silicon, silicon oxide, silicon nitride, gallium arsenide, silicon carbide, aluminum, aluminum oxide, aluminum nitride, copper, and tungsten.

Citation Information

Patent Citations

  • Social Advertisements and Other Informational Messages on a Social Networking Website, and Advertising Model for Same

    US20110029388A1

  • Polyacrylated oligomers in ultraviolet curable optical fiber coatings

    US4608409A

  • Process for the manufacture of zirconium oxide hydrate from granular crystallized zirconium oxide

    US5002749A

  • Method for directly depositing metal containing patterned films

    US5534312A

  • Microstructure-bearing articles of high refractive index

    US6844950B2